2022
DOI: 10.4103/jfmpc.jfmpc_730_22
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of new-onset seizures in adult patients of different age groups presenting to the emergency department in North India and their outcomes

Abstract: A BSTRACT Introduction: Seizures are one of the most common neurological emergencies encountered in both urban and rural India. There is only limited research work on the etiology of new-onset seizures in adult patients of different age groups presenting to the emergency department, especially from the Indian sub-continent. A new-onset seizure can be the first presentation of stroke, or it may be a symptom of brain infections, metabolic abnormality, brain tumor, systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 11 publications
3
2
2
Order By: Relevance
“…These results are different from Bhatia and colleagues [14] who had reported that the most common seizure type of seizure was generalized tonic-clonic seizures, present in 98.9% of patients, whereas focal seizures were seen in 1.1%, and the percentage of patients having generalized tonic-clonic seizures was more than those in our study, probably because all patients in their study were enrolled from emergency departments where most of the active epilepsy patients brought to emergency room are those having the grand mal presentation (generalized tonic-clonic seizures), particularly when they take the serial or status form.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…These results are different from Bhatia and colleagues [14] who had reported that the most common seizure type of seizure was generalized tonic-clonic seizures, present in 98.9% of patients, whereas focal seizures were seen in 1.1%, and the percentage of patients having generalized tonic-clonic seizures was more than those in our study, probably because all patients in their study were enrolled from emergency departments where most of the active epilepsy patients brought to emergency room are those having the grand mal presentation (generalized tonic-clonic seizures), particularly when they take the serial or status form.…”
Section: Discussioncontrasting
confidence: 96%
“…In our study 12.0% of the studied patients had normal computed tomography (CT) / magnetic resonance imaging (MRI) brain, and 88.0% had abnormal CT / MRI brain. Parallel to the results of our study, Bhatia and colleagues [14] showed that almost 72% had abnormal brain imaging and Sheikh and colleagues [17] stated that MRI showed abnormal findings in 59.7% of the patients.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations